ACTIV ATED CARBON FROM INDIGENOUS INFERIOR WOODS Part- V. Granular Activated Carbon Preparation and Liquid Phase Characterization (Biological Sciences - PJSIR, 2022)
The effect of zinc chloride in different impregnation ratios on various physical and chemical properties of granularactivated carbon prepared from saw dust (0.250-0.473 mm) of 'Babul' (Acacia arabica) has been studied. It has beenfound that zinc chloride acts both as an activating agent as well as a binder during this process. The suitability ofgelatinous mass used for granulization with different impregnation ratios has been studied and an appropriate ratioestablished. The activity of the product has been evaluated in liquid phase against adsorbates of different moleculardimensions. Granular carbon suitable for adsorption of small and larger molecules (micro and meso) may be preparedby chemical impregnation method.